A major plant practice at Mead Johnson Nutritionals, a Division of Bristol-Myers Squibb Phils. 2309 Don Chino Roces Avenue, Makati City - Genise, Winter O. (2006)
The plant practice was conducted at Mead Johnson Nutritionals, a division of Bristol-Myers Squibb at Don Chino Roces Avenue Extension, Makati City from April 11 to June 1, 2005. For 288 hours, the trainee was exposed in the manufacture of infant and follow-on formula. She was directly involved in the dispensing of raw materials, quality assessment of finished goods through organoleptic and physical testing, review of documents and warehouse operations. Also, she witnessed the application of principles linking the operations of different equipment. Information about the company and the products were obtained and through all the activities, the trainee developed interpersonal relations with persons people from different levels of organizations